Pengaruh Metode Discovery Learning Terhadap Hasil Belajar Matematika Materi Bangun Datar Pada Siswa Kelas V SD - Auliya Febriana; Aghna Ikhtiara Hendra Rachman; Afrilina Raudhotul Jannah; Nur Wiji Sholikin (Yayasan Insan Mulia Bima, 2026)
This study was inspired by fifth-grade elementary school students' poor performance in mathematics, particularly in plane figures, due to the widespread use of the lecture method, which tends to make students docile and unmotivated. Therefore, the purpose of this study is to ascertain how the Discovery Learning approach affects the academic performance of thirty fifth-grade students at SDIT Tahfidz Bintangku in Probolinggo City, particularly in the field of plane figures. Any causal interpretation must take into consideration risks to internal validity because the approach was a quantitative study using a pre-experimental design of the one-group pretest-posttest type without a control group. The study used written pretest and posttest instruments, whose reliability was evaluated using Cronbach's Alpha (α = 0.87, high category) and whose validity was evaluated using Pearson's product-moment correlation. With a significance level of 0.000 < 0.05 and an average N-gain Score of 0.42 (moderate category) and a Cohen's Effect Size of 1.23 (large effect category), data analysis using the Paired Samples t-Test with IBM SPSS Statistics showed an increase in the mean score from 40.83 on the pre-test to 65.73 on the post-test; as a result, H1 is accepted. Therefore, it can be said that the Discovery Learning approach significantly improves fifth-grade elementary school students' learning outcomes in the area of plane figures; however, given the limitations of the research design, which did not include a control group, causal generalizations should be made with caution.